Serotonin/GABA receptors modulate odor input to olfactory receptor neuron in locusts - Lv, Mingyue; Xu, Xiao; Zhang, Xinyang; Yuwen, Bo; Zhang, Long (Frontiers in Cellular Neuroscience, 2023)
Introduction Serotonin (5-hydroxytryptamine; 5-HT) and GABA (γ-aminobutyric acid) are involved in the regulation of behaviors in the central nervous system. However, it remains unclear whether they modulate olfaction in the peripheral nervous system, and how they modulate olfaction. Methods and results One 5-HT receptor sequence (Lmig5-HT2) and one GABA receptor sequence (LmigGABAb) were identified in locust antennae by transcriptome analysis and polymerase chain reaction experiments. In situ hybridization localized Lmig5-HT2 to accessory cells, while LmigGABAb was localized to olfactory receptor neurons (ORNs) in locust chemosensilla. Single-unit electrophysiological recordings combined with RNA interference (RNAi) experiments indicated ORNs of locusts with knockdown of Lmig5-HT2 (ds-Lmig5-HT2) and LmigGABAb (ds-LmigGABAb) to some odors had significantly higher responses than wild-type and control locusts in the dose-dependent responses. Moreover, the gaps between the responses of ORNs of RNAi ones and those of wild-type and ds-GFP enlarged with an increase in concentrations of odors. Discussion Taken together, our findings suggest that 5-HT, GABA, and their receptors exist in the insect peripheral nervous system and that they may function as negative feedback to ORNs and contribute to a fine-tuning mechanism for olfaction in the peripheral nervous system.